Modul Pengembangan Modul Pembelajaran Antilock Brake System (ABS) Sepeda Motor Di SMK Negeri 1 Jamblang : A. Pendahuluan B. Metode C. Hasil dan Pembahasan D. Simpulan E. Daftar Rujukan - arif sodik romadhon (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This development research aim to produce an module for a motorcyle ABS brake system and test the fesibility of an module motorcyle ABS brake ststem for class XI students of Motorcyle Busines Engineering at SMK Negeri 1 Jamblang. Research on the development module uses the Four-D model which consists of the define/define stage, the planning/design stage, the development/develop stage, and the dissemination/disseminate stage. This development research involves material, media, subject teachers, expert as well as students as research subject and research objects in the form of assesments and responses to the feasibility of module. The use of a questionnaire in the form of quantitative desqriptive data analysis became a data colection technique in this development research. The results in the module development research through the fesibility of the material expert test showed a feasibility gain of 76% with a “feasible” classification, media expert showed a feasibility gain of 83% with a “feasible” classification, subject teachers expert showed a feasibility gain of 89% with a “very feasible” classification, category and the result of the assesment of the limted trial gained a percentage of 86% in the “verry veasible” category and the result og large-scale trials gained 87% in the “very feasible” category. From the trial of the results of the feasibility of the module, the results of the feasibility of using the module ABS brake system in the teacing and learning proces of motorcycle chassis maintenance.